2021
DOI: 10.1136/bmjopen-2021-051053
|View full text |Cite
|
Sign up to set email alerts
|

Clinical communication in inflammatory bowel disease: a systematic review of the study of clinician–patient dialogue to inform research and practice

Abstract: ObjectivesThis systematic review aims to investigate what is currently known about the characteristics of interactions between patients with inflammatory bowel disease (IBD) and their clinicians and its effect on patient outcomes.Data sourcesScopus, PubMed, Embase, Communication Abstracts, Health & Society, Linguistics and Language Behaviour Abstracts and PsycINFO were systematically searched from inception to June 2021.Study eligibility criteriaPeer-reviewed journal articles and book chapters in English i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Out of the 361 documents found in the literature related to basic palliative care training for nurses, five documents were selected. These include the National Consensus Project’s Clinical Practice Guidelines for Quality Palliative Care (NCP Guidelines) 4th edition [ 41 ], Competencies And Recommendations for Educating Undergraduate Nursing Students Preparing Nurses to Care for the Seriously Ill and their Families from the End-of-Life Nursing Education Consortium (ELNEC) [ 42 ], Foundations in palliative care: A Program of Facilitated Learning for Care Home Staff of the Macmillan Cancer Relief [ 43 ], Nursing competencies in palliative care [ 18 ] and Recommendations about training in palliative care in nursing degree of the Spanish Palliative Care Nurses Association [ 17 ]. The NCP Guidelines establish training in eight domains, and ELNEC adds another three.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 361 documents found in the literature related to basic palliative care training for nurses, five documents were selected. These include the National Consensus Project’s Clinical Practice Guidelines for Quality Palliative Care (NCP Guidelines) 4th edition [ 41 ], Competencies And Recommendations for Educating Undergraduate Nursing Students Preparing Nurses to Care for the Seriously Ill and their Families from the End-of-Life Nursing Education Consortium (ELNEC) [ 42 ], Foundations in palliative care: A Program of Facilitated Learning for Care Home Staff of the Macmillan Cancer Relief [ 43 ], Nursing competencies in palliative care [ 18 ] and Recommendations about training in palliative care in nursing degree of the Spanish Palliative Care Nurses Association [ 17 ]. The NCP Guidelines establish training in eight domains, and ELNEC adds another three.…”
Section: Resultsmentioning
confidence: 99%
“…Both patients and physicians reported suboptimal control less frequently than it was detected by objective assessment using the red flags. Limited alignment between HCP and patient-reported suboptimal control was also observed, potentially due to different emphasis in IBD care components between the groups, indicating the need for effective communication between patients and HCPs [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patient–physician relationship in IBD has been studied in the past. 27 , 28 Karimi et al reported that there are still a lack of studies that evaluate the impact of a positive or negative patient–physician relationship on outcomes in IBD. 28 Nevertheless, trust in the provider appears to be an important issue for IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 28 Karimi et al reported that there are still a lack of studies that evaluate the impact of a positive or negative patient–physician relationship on outcomes in IBD. 28 Nevertheless, trust in the provider appears to be an important issue for IBD patients. 27 This seems to be the case in Lebanese IBD patients to a greater degree.…”
Section: Discussionmentioning
confidence: 99%